The Role of Psychological Empowerment: The Relationship Between Servant Leadership and Sustainable Performance of Community Institutions - R. Joko Sugiharjo; Rr Niken Purbasari; Abdul Rahmat; Paijan Paijan (Dinasti Publisher, 2025)
This study investigates how servant leadership influences sustainable performance in community institutions in Meruya Selatan Village, with psychological empowerment as a mediating variable. Centered on Social Exchange Theory the relationship between these factors is an important consideration for the sustainability of community institutions. The approach that will be used to complete this study is quantitative with SEM data analysis methods. Sample selection through a random sampling technique approach that has been collected based on the distribution of questionnaires, including: field officers, Community Early Warning Forum, Handling of Public Infrastructure and Facilities, Village Staff, Deliberative Institutions, Entrepreneurs, employees, and laborers with a total sample size of 137. The results of this study reveal that servant leadership produces a negative and insignificant effect in influencing institutional performance, while the direct relationship between servant leadership and psychological empowerment, as well as psychological empowerment with institutional performance is positive and significant. The most important thing as the main focus of the results of this study is the role of psychological empowerment as a mediator is able to provide a positive and significant effect on the relationship between servant leadership and institutional performance. The resulting mediation model is a superior model design or full mediation. This model is an effective institutional model mechanism as a form of contribution to the implementation of strategic decision-making, especially in the context of community institutions.